Anthropology of Conservation in Spain. Review and perspectives - Beltran Costa, Oriol; Santamarina Campos, Beatriz (Revista de Antropología Social, 2016)
In this article we present a review of the Anthropology of Conservation in Spain. During the last decades the protection of natural spaces has exponentially increased its territorial coverage worldwide. At the same time than this patrimonialization of nature was expanded, ethnographic research on protected areas have also become common, especially as part of Environmental Anthropology. The aforementioned bibliography has highlighted the multiple analytical dimensions that emerge from these new territorial policies of regulation, appropriation, and commodification of nature. In the piece, we conduct an exhaustive review of the literature produced as a consequence of this interest in our country on protected areas, underscoring its main contributions, characteristics, and weaknesses. We intent to reflect on its future, contribute to avoid repetition, and help to its development
Keywords: Protected areas; ethnography; anthropology of conservation; patrimonialization of nature.